Newfoundland and Labrador Maligned: Taking Stock of Nutritional Health in Rural Newfoundland and Labrador, 1912-1949 - Strikwerda, Eric (Acadiensis)

(untitled) (The Department of History of the University of New Brunswick, 2018)
This article explores the relationship between the ways (mainly) outsiders characterized Newfoundlanders’ nutritional health and the bearing those characterizations had on Newfoundland’s constitutional destiny in the lead up to Confederation in 1949. Through the first half of the 20th century, Newfoundlanders’ nutritional health was the subject of numerous scholarly inquiries. Many of these inquiries concluded that Newfoundlanders themselves were often the authors of their own poor nutritional health. Not surprisingly, this conclusion proved deeply offensive to many Newfoundlanders – so much so that by mid-century the issue of nutrition emerged as no small factor in Newfoundland’s Confederation debates."